Anteseden dan Konsekuensi Implementasi Sistem Akrual Basis (Studi Empiris Pada Satuan Kerja Perangkat Daerah Provinsi Lampung) - Lego Waspodo; Dona Primasari; Indayani Indayani (Program Magister Akuntansi Unsyiah, 2017)
This study examined the antecedent variables of implementation accrual basis system and its consequences. The antecedent variables are : adaptation and the manager support. The Concequences are satisfaction and performances of the officer . This research represented the empirical test which was usingconvienence sampling technics in data collection. Data were collected from 107 officers of the local government in Lampung province. Data analysis used was Structural Equation Model (SEM) with using program AMOS 20.0. Result of hypothesis examination indicated that four hypothesis raised are accepted.KEYWORDS : Adaptation officer, manager support, implementation accrual basis system, satisfaction and performance officer.